On manimax theory in two Hilbert spaces - E. M. El-Kholy; Hanan Ali Abdou (International Journal of Mathematics and Mathematical Sciences)
In this paper, we investigated the minimax of the bifunction J:H1(Ω)xV2→RmxRn, such that J(v1,v2)=((12a(v1,v1)−L(v1)),v2) where a(.,.) is a finite symmetric bilinear bicontinuous, coercive form on H1(Ω) and L belongs to the dual of H1(Ω).